Organizational ethics : a practical approach - Johnson, Craig E. (Thousand Oaks, CA : SAGE Pub, 2012)
Ethical perspectives -- Components of personal ethical development -- Ethical decision making and action -- Ethical interpersonal communication -- Exercising ethical influence -- Ethical conflict management and negotiation -- Improving group ethical performance -- Leadership ethics -- Followership ethics -- Building an ethical organizational culture -- Managing ethical hotspots in organizations -- Promoting organizational citizenship in a global society.
Includes bibliographical references and index.
Keywords: Business ethics; Corporate culture; Ethics; Ethics, Business; Organizational Culture